A review on smart self-sensing composite materials for civil engineering applications - Rana, Sohel (2016)
Self-sensing composites are becoming highly attractive for civil engineering applications to improve the safety and performance of structures. These smart composites show a detectable change in their electrical resistivity with applied stress or strain and this unique characteristic make them useful for health monitoring of structures. Till date, different forms of carbon composites, i.e. short fibre, continuous fibre, particles, nano fibres, nanotubes, etc. have been utilized for this purpose. In this context, the present paper reports an overview of different self-sensing composite systems used for the health monitoring of civil engineering structures.